Not One, but Many Critical States: A Dynamical Systems Perspective - Gross, Thilo (Frontiers in Neural Circuits, 2021)
The past decade has seen growing support for the critical brain hypothesis, i.e.~the possibility that the brain could operate at or very near a critical state between two different dynamical regimes. Such critical states are well-studied in different disciplines, therefore there is potential for a continued transfer of knowledge. Here I revisit foundations of bifurcation theory, the mathematical theory of transitions. While the mathematics is well known it's transfer to neural dynamics leads to new insights and hypothesis.